2010
DOI: 10.1177/230949901001800218
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Wound Infection in HIV-Positive Patients Undergoing Surgery for Orthopaedic Trauma

Abstract: Identification of risk factors may help minimise morbidity in HIV-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 22 publications
(32 reference statements)
5
33
0
8
Order By: Relevance
“…Abalo et al [18], at a median follow-up period of 27 months (range 19-41 months), demonstrated very high incidence of late implant sepsis (39%) in 36 HIV-positive patients. Lukhele et al reported a case of late implant sepsis at 4 years in a seropositive patient who had previously undergone spine stabilization surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Abalo et al [18], at a median follow-up period of 27 months (range 19-41 months), demonstrated very high incidence of late implant sepsis (39%) in 36 HIV-positive patients. Lukhele et al reported a case of late implant sepsis at 4 years in a seropositive patient who had previously undergone spine stabilization surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Among 39 patients with HIV undergoing implant surgery, there were 6 cases of wound infection, with 5 cases resolving after antibiotics and 1 case progressing to a deep chronic infection [19,20]. A study of 36 patients with HIV undergoing orthopedic trauma surgery identified 14 cases of postoperative wound infection, of which 12 resolved after debridement and antibiotics and 2 progressed to chronic osteomyelitis [21]. Among 34 patients with HIV who underwent 44 total hip arthroplasties, there were 2 deep infections identified at 59 and 64 months postoperatively, with both resolving after revision surgery with extensive debridement and the placement of an antibiotic spacer [11].…”
Section: Discussionmentioning
confidence: 99%
“…This same definition of an ASEPSIS score of greater than 10 was used by the Malawi group [31]. However, the definition used in the other studies was not consistent [32,24,[33][34][35][36][37].…”
Section: Closed Fracturesmentioning
confidence: 99%
“…Eight authors studied non-union in closed fractures, with a mix of prospective [48,50,53] and retrospective studies [35,54]. (Table 5) The rates of non-union were 0% in 26 HIV-positive ART naïve patients that were clinically and radiologically closed femoral fractures that had undergone intramedullary nailing, however the method of evaluation of non-union was not described.…”
Section:  Non-union In Closed Fracturesmentioning
confidence: 99%